A Vibration Analysis of a 6 Axis Industrial Robot Using FEA. (2017) - Sahu, Supriya; Choudhury, B.B.; Biswal, B.B.
Abstract: Robotic Manipulators are widely used in different fields of industries and with different applications. They are used for the purpose of saving time, effort, and sometimes save the life of the human being. The current paper shows a vibration analysis of frequencies of robot. The different modes of frequencies for the robot having crack and without having crack based are analyzed on the finite element method (FEM). In order to improve the efficiency of an industrial robot, a finite element model of the robot is established by utilizing the software of ANSYS Workbench. Where the model is designed in CATIA V5 with crack and without crack and the frequencies at three different modes are obtained. Finally, the weak parts of the robot arm are found out and relative improving suggestion is put forward, which laid foundation for the optimized design.